Aplikasi Trigona (Tetragonula) laeviceps sebagai Agen Penyerbuk pada Sistem Tumpang Sari Buncis dan Tomat di dalam Rumah Kaca - NOVITASARI; LEKSIKOWATI, SOVIA SANTI; EKA PUTRA, RAMADHANI; ROSMIATI, MIA; KINASIH, IDA; ZAKIYATUN USNA, INAYATI; SETYARNI, EKA; ANJARNISA RUSTAM, FAJRINA (Jurnal Sumberdaya Hayati, 2018)
Greenhouse is widely applied to provide protection against pest and harsh environment condition and most farmers usually planted mixed crops inside. However, this system creates an isolation to pollination which responsible for fruit production. In this study, local domesticated stingless bees, Trigona (Tetragonula) laeviceps, was applied as pollinator for two crops, beans (Phaseolus vulgaris L.) and tomatoes (Solanum lycopersicum L.) planted as mixed crops inside greenhouse. The benefit of the bees was measured as pollination success and quality of the crops produced (size and weight). Tomato flowers received no visit from both wild pollinators (all was Apis cerana) and stingless bees while in bean flowers, A. cerana exhibited more and longer visits to flower than T. laeviceps albeit lower number of flowers visited. The pollination efficiency between wild pollinator and T. laeviceps for beans (both at 41%) while self pollination produced better pollination efficiency for tomatoes planted at open field (84% compared to 71%). Beans planted at open field produced better products (bigger size and heavier) while tomatoes produced lesser quality although the differences were not significant. Based on this study, T. laeviceps may applied as pollinator agent in greenhouse and for mixed crops of beans and tomatoes.